2016
DOI: 10.1002/jqs.2849
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy, location of origin and health status of proboscideans from Western Canada investigated using stable isotope analysis

Abstract: We investigated the application of stable isotope analysis of proboscidean remains (collagen in bone/dentin/cementum and structural carbonate in enamel bioapatite) for genus-level identification of isolated specimens, assessment of geographic origins, and testing for nutritional stress. Mammoths (Mammuthus sp.) tended to have higher δ 15 N col and lower δ 13 C col than mastodons (Mammut americanum), but differences were not significant in every location.Determining the genus of isolated specimens may be possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 181 publications
(190 reference statements)
2
2
0
Order By: Relevance
“…The type-1 collagen scaffolding of these permafrost bones has undergone limited diagenesis relative to the extensive in-situ polymerization/carbonization observed for soft tissue specimens of earlier geologic strata [18,19,21,22,79]. This agrees with prior studies on bulk permafrost bone extracts that have reported C:N ratios of ~2.9-3.6, implying relatively minimal alteration of the collagen [46][47][48]. Likewise, paleoproteomic sequencing studies of permafrost bone generally report sequence coverage for both peptide chains of type-1 collagen (α1 and α2) >50-60% [40,44,45], roughly comparable to what is reported for extant bone [49,50].…”
Section: Figure 3 Hydroxyproline-related Secondary Ion Peak For Colla...supporting
confidence: 85%
See 3 more Smart Citations
“…The type-1 collagen scaffolding of these permafrost bones has undergone limited diagenesis relative to the extensive in-situ polymerization/carbonization observed for soft tissue specimens of earlier geologic strata [18,19,21,22,79]. This agrees with prior studies on bulk permafrost bone extracts that have reported C:N ratios of ~2.9-3.6, implying relatively minimal alteration of the collagen [46][47][48]. Likewise, paleoproteomic sequencing studies of permafrost bone generally report sequence coverage for both peptide chains of type-1 collagen (α1 and α2) >50-60% [40,44,45], roughly comparable to what is reported for extant bone [49,50].…”
Section: Figure 3 Hydroxyproline-related Secondary Ion Peak For Colla...supporting
confidence: 85%
“…Both the permafrost and extant specimen C:N ratios were within the range 2.9-3.6, which has historically been accepted as indicating well-preserved collagen. Values for %C and %N (by mass) ranged from 41.0-46.0% and 15.2-17.1%, respectively, which is likewise consistent with the collagenous scaffolding having undergone minimal diagenesis [46][47][48]65]. Measurements of δ 13 C and δ 15 N are also reported; while the obtained values are consistent with prior values obtained from permafrost megafaunal bones, they are more so related to organismal diet/trophic-level and thus are not further discussed [46][47][48].…”
Section: Permafrost Specimens and Elemental/isotopic Analysissupporting
confidence: 66%
See 2 more Smart Citations